2005
DOI: 10.1109/tpami.2005.170
|View full text |Cite
|
Sign up to set email alerts
|

A new image representation algorithm inspired by image submodality models, redundancy reduction, and learning in biological vision

Abstract: Abstract-We develop a new biologically motivated algorithm for representing natural images using successive projections into complementary subspaces. An image is first projected into an edge subspace spanned using an ICA basis adapted to natural images which captures the sharp features of an image like edges and curves. The residual image obtained after extraction of the sharp image features is approximated using a mixture of probabilistic principal component analyzers (MPPCA) model. The model is consistent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…An image feature model of perception was suggested by Mojsilovic et al (2002), where it was suggested that humans view or recall an image by its dominant colors only, and areas containing small, nondominant colors are averaged by the human visual system. Other examples of the term perception defined in the context of psychophysics have also been given (Wilson et al 1997;Dempere-Marco et al 2002;Kuo and Johnson 2002;Wandell et al 2002;Wang et al 2004;Balakrishnan et al 2005;Qamra et al 2005).…”
Section: Quantifying Nearness In Visual Spaces 39mentioning
confidence: 99%
“…An image feature model of perception was suggested by Mojsilovic et al (2002), where it was suggested that humans view or recall an image by its dominant colors only, and areas containing small, nondominant colors are averaged by the human visual system. Other examples of the term perception defined in the context of psychophysics have also been given (Wilson et al 1997;Dempere-Marco et al 2002;Kuo and Johnson 2002;Wandell et al 2002;Wang et al 2004;Balakrishnan et al 2005;Qamra et al 2005).…”
Section: Quantifying Nearness In Visual Spaces 39mentioning
confidence: 99%
“…Establishing an emulating cortex recognition system has always been a challenging issue. References [11][12][13] have investigated the biological feasibility of explaining aspects of higher-level visual processing. The aim of object recognition can be understood by representing objects as collections of view-specific features and taking the view that the basic recognition processes occur in a bottom-up way.…”
Section: Nomenclaturementioning
confidence: 99%
“…This last alternative can be implemented by approximation [10], image simplification at early stages [11], sparse representation of the scene [12] or hierarchical processing and resource optimization [13]. For systems running on a low power budget, energy efficiency is required, therefore power consumption needs to be minimized:…”
Section: Energy Efficiency In Vision Chipsmentioning
confidence: 99%